2017
DOI: 10.5194/acp-2017-646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison and evaluation of anthropogenic emissions of SO<sub>2</sub> and NO<sub>x over China

Abstract: Abstract. Bottom-up emission inventories provide primary understanding of sources of air pollution and essential input of chemical transport models. Focusing on SO 2 and NO x , we conducted a comprehensive evaluation of two widely-used anthropogenic emission inventories over China, ECLIPSE and MIX, to explore the potential sources of uncertainties and 15 find the clues in improving emission inventories. We first compared the activity rates and emission factors used in two inventories, and investigated the reas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 18 publications
(31 reference statements)
0
9
0
1
Order By: Relevance
“…Nitrogen dioxide easily undergo chemical reactions. The main anthropogenic source of NO 2 formation is burning of any fossil types of fuel (motor-vehicles, power generation, manufacturing facilities) ( Li et al, 2018 ). The higher air concentrations of NO 2 are observed in large Polish cities (Krakow, Warsaw, Wroclaw) as compared to other cities of the country; it is associated with high motor-vehicle traffic.…”
Section: Resultsmentioning
confidence: 99%
“…Nitrogen dioxide easily undergo chemical reactions. The main anthropogenic source of NO 2 formation is burning of any fossil types of fuel (motor-vehicles, power generation, manufacturing facilities) ( Li et al, 2018 ). The higher air concentrations of NO 2 are observed in large Polish cities (Krakow, Warsaw, Wroclaw) as compared to other cities of the country; it is associated with high motor-vehicle traffic.…”
Section: Resultsmentioning
confidence: 99%
“…NMVOC speciation in MEIC is based on Chinese emission profiles . Previous evaluations showed that MEIC is able to represent the magnitudes and seasonal/interannual variation of Chinese emissions. , Anthropogenic emissions outside China are from MIX-Asian inventory for 2010 . Natural precursor emissions from vegetation, soil, and lightning are calculated online in GEOS-Chem (Figure S2).…”
Section: Methodsmentioning
confidence: 99%
“…Intercontinental Chemical Transport Experiment Phase B)排放清单 [48] 、中国多尺度排放清单模型 MEIC(http://meicmodel.org/) [62] 、亚洲人为源排放清单 MIX [46] 、北大全球尺度等综合排放清 单 [63] 以及生物质燃烧、机动车、电厂、工业源、非道路移动、天然源、NH 3 排放、NOx 排放、 [49,[64][65][66][67][68][69][70][71] 。 相 比 TRACE-P(the Transport and Chemical Evolution over the Pacific) [47] 和 REAS(Regional Emission Inventory in Asia)等东亚排放清单 [72] , 我国学者建立的国家排放清单采用了更为详细的活动水平数据和更多的本地排放因子,空间分 辨率最高达到 1km [73] ,能更好的反应我国污染源的排放特征。在区域和省级尺度方面,前体物 排放清单研究主要集中在华东地区(以长三角为主) [45,55] 、华南地区(以珠三角为主) [43,50] 、 华北地区(以京津冀为主) [74] [75] [76] 、以及西南地区(以川渝为主) [77] 率先探索了城市排放清单编制工作。随后,京津冀大气污染传输通道上的"2+26"城市也开始编 制城市排放清单 [78] 。为此,2014 年之后发表的城市尺度排放清单文献迅速增加,并且集中在我 国华北地区(以京津冀为主)和华东地区(以长三角为主) (图 1) 。空间分辨率方面,超过 [50,79,80] ,并进行优化 [81,82] 。近年来 也有研究通过同位素源解析校验 BC 排放的源结构 [83] 。总体上,SO 2 排放清单与观测数据或者 同类型清单具有较好的一致性,而 NOx 排放清单则存在一定差异性,可能与电厂、工业锅炉和 移动源的排放的不确定性较大有关 [84][85][86][87] 。此外,反演前后的 BC 排放清单也存在较大差异,表 明 BC 排放清单还需要进一步改进 [88][89][90][91] 。 相比于 SO 2 、NOx 和 BC,大气 NH 3 容易受到大气反应和干湿沉降影响,其排放清单校验 与评估也更为困难,相关研究还较为匮乏。现有研究主要利用反演校验和基于稳定氮同位素溯 源方法校验评估 NH 3 排放。例如,Lei 等人 [92] 利用我国的大气氨观测网络数据和卡尔曼滤波反 演模型优化了中国 NH 3 月排放特征;Pan 等人 [93] 利用稳定氮同位素溯源技术发现非农业源对大 气环境 NH 3 的贡献可能超过农业源,机动车尾气和工业氨气排放的强度有可能被低估。 不同研究建立的 ...…”
Section: 前体物排放清单编制与建立实践unclassified